PERANCANGAN RODA GIGI LURUS, RODA GIGI MIRING DAN RODA GIGI KERUCUT LURUS BERBASIS PROGRAM KOMPUTASI - Erinofiardi . (JURNAL MECHANICAL, 2013)
Gears are used to transmit torque and angular velocity in a wide variety of applications. There is also a wide variety of gear types to choose from.The simplest type is spur gears, designed to operate on parallel shafts,while others for nonparallel shafts are usually using helical, bevel and worm gears. Design of gearset is base on given parameters, tables, graphs and standard which needs much time for calculating if done manually. Based on that drawback it needs computational design to safe time so that gives more benefit. Computer program’s we made  can get accurate design which only has small different compare to conventional design method. Those differents are surface stress for idler-gear mesh and surface stress for pinion-idler mesh. Rounding values in conventional design cause it, while computational design  doesnot needs that step.  Key words : Gears, design, conventional, computational